Analisis Implementasi Aplikasi Accurate Pada PT MCG - Dinny Irfani; Irawan Irawan; Nurmala Nurmala (Jurnal Ilmiah ESAI, 2018)
The purpose of this final report is to analyze the implementation of Accurate application on PT MCG. The data used include the reports produced by the Accurate application that is the income statement of PT MCG, and the output produced by Accurate application. The author uses qualitative methods to provide information about the menus contained in the application Accurate, and the menus in the application Accurate used PT MCG and its function for PT MCG. The Accurate application on PT MCG has deficiencies in the resulting financial reports. The Accurate application used by PT MCG only results in the income statement. The resulting profit and loss statement has not complied with the applicable regulations, since the income statement of PT MCG does not represent costs as one of the components  of the income statement of the company. The use of Accurate application  on  PT  MCG  has  not  been  optimal  in  the  preparation  of  the  company's financial  statements  in  particular  can  not  display  the  statement  of  financial  position (balance  sheet). The authors suggest that companies  use the more comprehensive  new version of the Accurate versiter application. Keywords: Accurate, Income Statement, PT MCG.